Identificação de áreas de interesse para a conservação da biodiversidade na porção profunda da Bacia de Campos : fundamento para uma rede de áreas protegidas - Almada, Gustavo Vaz de Mello Baez (2016)
Brazil, as signatory to the Convention on Biological Diversity, is committed to the goal of protecting at least 10% of its marine area in a representative system of marine protected areas (MPAs) by the year of 2020. However, Brazil is currently protecting no more than 1.5%. This study aims to identify areas of interest for the conservation of benthic biodiversity in the deep portion (depth > 200 m) of the southeastern Brazilian continental margin, which is the main oil and gas exploitation area of Brazil. We have employed benthic habitats as a proxy for benthic biodiversity distribution, setting the representation of 30% of the area of all benthic habitats in the study area as the conservation goal. Habitats characterization was developed from a nested hierarchical scheme, utilizing abiotic surrogates that strongly influence biodiversity distribution in the deep sea: depth; geomorphology; sediment grain size; and sediment total organic carbon. As result, 42 habitat types were mapped in the study area: 21 characterized by sedimentary continental slope; 11 by submarine canyon; 6 by cold water coral reef; and 4 by seamount. Marxan software was used to support the design of a MPA network with minimal overlap to areas leased to the oil industry, applying three scenarios: 1 - without spatial constraints for location of MPAs; 2 - restricting MPAs location to nonleased areas; 3 - restricting the overlap of MPAs within a 5 km buffer around oil production platforms. Also, in scenario 3 benthic macrofaunal diversity was used as a secondary driver for the location of MPAs, in order to favor the selection of higher diversity areas. In scenario 1 it was possible to achieve the 30% representation target for all 42 habitats, but MPAs overlap with leased areas is 60% of the total leased areas within deep Campos Basin. In scenario 2 there was no overlap at all, but 15 habitat were represented below the 30% target. In scenario 3 all habitats achieved the 30% representation target while the overlap with leased areas was reduced to 5.5%, and still the total area for the MPA network is only 31.3% of the study area. The MPA network resulted in scenario 3 can be considered a good starting point for its effective creation by Brazilian authorities, preferably involving stakeholders in this process, in order to improve the ecological and social outcomes of biodiversity conservation.